Crude oil price, exchange rate and emerging stock market: evidence from India - Sahu, Tarak Nath; Bandopadhyay, Kalpataru; Mondal, Debasish (Penerbit Universiti Kebangsaan Malaysia, 2014)
Oil is one of the most important forms of energy and is a significant determinant of global economic performance. Commodities like oil are fairly homogeneous and internationally traded. The impact of dollar nominated oil prices on stock prices may not be quite relevant for Indian context. In this context, the study of crude oil prices in dollar terms along with the exchange rate would be more meaningful to understand the impact of oil prices on stock market. The study investigates the dynamic relationships between oil price, exchange rate and Indian stock market during 1993 to 2013. The estimated results of the Johansen’s cointegration test and vector error correction model suggest that there exist a long run cointegrating relationships between crude oil price and Indian stock indices, but it cannot be said with sufficient confidence that the direction of the relation in the long run is from the oil price to the Sensex. The Granger causality test also reveals that the volatility of stock prices in India can be explained to cause the movement of oil price and exchange rate in short run. The observed relationship between oil price and stock indices is not due to the effect of the exchange rate fluctuations, because the change in exchange rate has no significant impact on oil prices or stock prices in India during the study period. The variance decomposition analysis reveals that the Indian stock prices are strongly exogenous in the sense that the crude oil price or exchange rate explains only a very small portion of the forecast variance error of the market index. Finally, from the impulse response functions analysis it is noticed that a positive shock in one variable have a persistent and prolonged effect on other variables